Posttraumatic Stress Symptoms After Stroke: The Effects of Anatomy and Coping Style. Issue 6 (10th March 2022) - Ben Assayag, Einor; Tene, Oren; Korczyn, Amos D.; Solomon, Zahava; Bornstein, Natan M.; Shenhar-Tsarfaty, Shani; Seyman, Estelle; Niry, Dana; Molad, Jeremy; Hallevi, Hen
Abstract : Background: Posttraumatic stress disorder (PTSD) can be triggered by life-threatening medical emergencies, such as stroke. Data suggest that up to 25% of stroke survivors will develop PTSD symptomatology, but little is known about predisposing factors. We sought to examine whether neuroimaging measures and coping styles are related to PTSD symptoms after stroke. Methods: Participants were survivors of first-ever, mild-moderate ischemic stroke, or transient ischemic attack from the TABASCO study (Tel Aviv Brain Acute Stroke Cohort). All participants underwent a 3T magnetic resonance imaging at baseline and were examined 6, 12, and 24 months thereafter, using neurological, neuropsychological, and functional evaluations. At baseline, coping styles were evaluated by a self-reported questionnaire. PTSD symptoms were assessed using the PTSD checklist. Data were available for 436 patients. Results: Forty-eight participants (11%) developed probable PTSD (PTSD checklist ≥44) during the first year after the stroke/transient ischemic attack. Stroke was more likely to cause PTSD than transient ischemic attack. Stroke severity, larger white matter lesion volume, and worse hippocampal connectivity were associated with PTSD severity, while infarct volume or location was not. In a multivariate analysis, high-anxious and defensive coping styles were associated with a 6.66-fold higher risk of developing poststroke PTSD ([95% CI, 2.08–21.34]; P <0.01) compared with low-anxious and repressive coping styles, after adjusting for age, education, stroke severity, brain atrophy, and depression. Conclusions: In our cohort, PTSD was a common sequela among stroke survivors. We suggest that risk factors for PTSD development include stroke severity, white matter damage, and premorbid coping styles. Early identification of at-risk patients is key to effective treatment.